Farmer business school with climate change and gender perspective in agroforestry context: Learning guide. - International Potato Center; Department of Environment and Natural Resources, Philippines (International Potato Center, 2018)
This guide is a participatory action learning process that involves farmer groups’ participation in agricultural value chains. As part of capacity strengthening, it comprises a series of group-based experiential learning activities over a production-marketing cycle while interacting with other chain actors and stakeholders. As a tangible outcome, the farmer-participants are expected to have actual business initiated or strengthened upon completing the learning process. The guide aspires to a more profitable pro-poor farm business through market oriented innovations that enhance trust, coordination and collaboration between farmers and other chain actors while empowering men and women farmers, thus ultimately contributing to sustainable livelihoods of targeted farming households.